MENINGKATKAN HASIL BELAJAR SISWA KELAS XA MADRASAH ALIYAH ALKHAIRAAT KOTA GORONTALO PADA MATERI REAKSI REDOKS DENGAN METODE KOOPERATIF TIPE NHT - Junus, Abdul Gias; Pikoli, Masrid; Suleman, Nita (Jurnal Entropi, 2009)
Student result of learning was still in the lower category. It must be solving. The way of how to solve the probem by applying cooperative learning method which type of Numbered Heads Together (NHT). The aim of this research is to improve student result of learning for the redoks material which applying cooperative learning method Numbered Heads Together (NHT) type. Sampel of the research is students on the tenth grade (XA) of MA Alkhairaat Gorontalo, in the 2008/2009 academic years. The sample consists of 18 students. This research was done/into the two cycles by involved a teacher partner as an observer. The criterion efficacy in this research is 85% student get ? 6,5 and observation toward the teacher and student activity get 75%. Based on this data, the result shows that cooperative learning method Numbered Heads Together (NHT) type can improve students result of learning by seeing students learning improvement which get mark more than 6,5 is 89%.